2012
DOI: 10.1186/1687-1499-2012-166
|View full text |Cite
|
Sign up to set email alerts
|

PluralisMAC: a generic multi-MAC framework for heterogeneous, multiservice wireless networks, applied to smart containers

Abstract: Developing energy-efficient MAC protocols for lightweight wireless systems has been a challenging task for decades because of the specific requirements of various applications and the varying environments in which wireless systems are deployed. Many MAC protocols for wireless networks have been proposed, often custommade for a specific application. It is clear that one MAC does not fit all the requirements. So, how should a MAC layer deal with an application that has several modes (each with different requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…De Mil et al have observed that real-life performance evaluations of WSN MAC protocols have shown that, depending on the traffic pattern and the packet interval, a given combination of MAC and routing is better under certain circumstances and can outperform other combinations. Therefore, the authors have proposed PluralisMAC, a generic multi-MAC framework able to switch among different MAC strategies [90]. To provide such flexibility, PluralisMAC is composed of two other frameworks within its architecture: Multi-MAC and Neighbour Management Framework (NMF).…”
Section: B Ieee 802154 Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…De Mil et al have observed that real-life performance evaluations of WSN MAC protocols have shown that, depending on the traffic pattern and the packet interval, a given combination of MAC and routing is better under certain circumstances and can outperform other combinations. Therefore, the authors have proposed PluralisMAC, a generic multi-MAC framework able to switch among different MAC strategies [90]. To provide such flexibility, PluralisMAC is composed of two other frameworks within its architecture: Multi-MAC and Neighbour Management Framework (NMF).…”
Section: B Ieee 802154 Networkmentioning
confidence: 99%
“…GNU Radio [131] Vanu Software Radio [134] Sora [133] CLAWS [121] RcUBE [47] WiMAC [46] UPS [44] LA-MAC [93] MAC Selection [17] Wireless & Theoretical IEEE 802. Hybrid MAC [87] T-MAC [4] S-MAC [6] PluralisMAC [90] λMAC [123] BiPS [125] Fig.…”
Section: Click Modularmentioning
confidence: 99%
“…In the beginning of this period, a critical event is transmitted from node 33 to node 55 (green line). A more thorough evaluation can be found in [15].…”
Section: Mac Logic In Pluralismacmentioning
confidence: 99%
“…Just above the HAL and IEEE-802.15.4 radio, we have PluralisMAC [15]. From a MAC layer point of view (IEEE 802.15.4 MAC), the specifications reveal that in the non-transmitting period (REST or STP mode), the radio should sleep as much as possible, while remaining capable of receiving triggers or sending a critical event.…”
Section: Tailored Sensor Communication Solutionsmentioning
confidence: 99%
“…In 2012, we published our pluralisMAC [8] framework. This allows for flexible switching between MAC protocols (so-called maclets).…”
Section: Contributionsmentioning
confidence: 99%